Fiscal Adjustment and the Costs of Public Debt Service: Evidence from OECD Countries - Christoph A. Schaltegger; Martin Weder (Center for Research in Economics, Management and the Arts (CREMA), 2010)
We use a panel of 21 OECD countries from 1970 to 2009 to investigate the effects of different fiscal adjustment strategies on long-term interest rates - a key fiscal indicator reflecting the costs of government debt service. A government confronted with high deficits and rising debt will sooner or later need to enact fiscal adjustments in order to avoid solvency problems. Over the last four decades, such measures taken by governments in OECD countries have varied in duration, size, composition and in their success to re-establish fiscal sustainability. Control-ling for various economic, fiscal and political factors, we find that the size and the composi-tion of a fiscal adjustment significantly affect interest rates as well as yield spreads. Adjust-ments that are relatively large and those that primarily depend on expenditure cuts lead to substantially lower long-term interest rates. However, periods of fiscal adjustments do not generally have an influence on interest rates, even if they were successful and led to lower deficits and debt levels. Instead, financial markets only seem to value strict and decisive measures - a clear sign that the government's pledge to cut the deficit is credible.
Keywords: E61; E63; H61; 330; Fiscal Adjustment; Consolidation Policy; government deficit; long-term interest rates